Vitales (2021)
VITALES is an urban renewal project located in the SantaFé neighborhood in Bogotá-Colombia. Its goal is to propose and create new recreational, cultural and living spaces for the community. It's coherent with its sourroundings and seeks the renewal of the south border of the Central Cemetry of Bogota through art, identity and heritage, being able to create new and exciting vital dynamics through architecture, honouring the neighborhood's past, answering to its present and projectcing its future.